Quasi-Stationary Strength of ECAP-Processed Cu-Zr at 0.5 T-m - Blum, Wolfgang; Dvorak, Jiri; Kral, Petr; Eisenlohr, Philip; Sklenicka, Vaclav (Metals, 2019)
The influence of the grain structure on the tensile deformation strength is studied for precipitation-strengthened Cu-0.2%Zr at 673K. Subgrains and grains are formed by equal channel angular pressing (ECAP) and annealing. The fraction of high-angle boundaries increases with prestrain. Subgrains and grains coarsen during deformation. This leads to softening in the quasi-stationary state. The initial quasi-stationary state of severely predeformed, ultrafine-grained material exhibits relatively high rate-sensitivity at relatively high stresses. This is interpreted as a result of the stress dependences of the quasi-stationary subgrain size and the volume fraction of subgrain-free grains.
CRIS-Team WoS Importer:2020-01-10